Bioactive Peptide Brush Polymers via Photoinduced Reversible‐Deactivation Radical Polymerization. (25th October 2019) - Sun, Hao; Choi, Wonmin; Zang, Nanzhi; Battistella, Claudia; Thompson, Matthew P.; Cao, Wei; Zhou, Xuhao; Forman, Christopher; Gianneschi, Nathan C.
Abstract: Harnessing metal‐free photoinduced reversible‐deactivation radical polymerization (photo‐RDRP) in organic and aqueous phases, we report a synthetic approach to enzyme‐responsive and pro‐apoptotic peptide brush polymers. Thermolysin‐responsive peptide‐based polymeric amphiphiles assembled into spherical micellar nanoparticles that undergo a morphology transition to worm‐like micelles upon enzyme‐triggered cleavage of coronal peptide sidechains. Moreover, pro‐apoptotic polypeptide brushes show enhanced cell uptake over individual peptide chains of the same sequence, resulting in a significant increase in cytotoxicity to cancer cells. Critically, increased grafting density of pro‐apoptotic peptides on brush polymers correlates with increased uptake efficiency and concurrently, cytotoxicity. The mild synthetic conditions afforded by photo‐RDRP, make it possible to access well‐defined peptide‐based polymer bioconjugate structures with tunable bioactivity. Abstract : Bio‐Bürsten : Eine photoinduzierte radikalische Polymerisation unter reversibler Deaktivierung (photo‐RDRP) eröffnet den Zugang zu einer neuen Klasse biologisch aktiver Peptidbürstenpolymere. Diese haben gut definierte Strukturen und einstellbare biologische Aktivitäten, was ihr immenses Potenzial für biomedizinische Anwendungen verdeutlicht.